PREDICTION OF LEUKAEMIA CANCER IMAGES USING PARALLEL SALIENCY ALGORITHM - SWARNALATHA P; ANBARASI M.; AMAN SHARMA; GANESH M (International Journal of Pharma and Bio Sciences, 2015)
Parallel Saliency algorithm is applied to solve the medical issues and to reduce the doctors’ work in the society. Prediction of specific area of a leukemia, cancer image can be made using a Parallel Saliency algorithm (PSA). Firstly, most affected phase of the leukemia cancer is possible by applying the parallel saliency algorithm over cancer images, secondly, PSA works in a multi-core environment in comparison with the existing saliency algorithm. As a whole, the paper deals with PSA, which provides efficient performance to researchers and scientist.